Simultaneous Determination of Two Effective Components in a Tractylodes macrocephala by RP-HPLC - Guo, Ying; Jin, Yong-Chun; Yuan, Ke (Asian Journal of Chemistry, 2012)
To establish a RP-HPLC method for simultaneous determination of two effective constituents (atractylenolide II and atractylenolide III) obtained from different district. Two effective constituents were simultaneously determined by RP-HPLC with WATERS XBridge C18 column (4.6 mm × 250 mm, 5 μm) by gradient elution (0-40 min, 60-100 % A) using methanol (A) and water (B) as the mobile phase. The flow rate was 1 mL min-1; the detection wavelength was 230 nm (0-17 min) for atractylenolide III and 276 nm (17-25 min) for atractylenolide II with column temperature at 30 ºC. Two effective constituents were separated clearly and respectively in 25 min, the linear ranges of atractylenolide II and atractylenolide III was 0.0301-0.1505 μg (r = 0.9998) and 0.0398-0.1990 μg (r = 0.9999), the average recoveries (n = 3) were 99.08 and 98.88, RSD % were 1.98 and 1.69 %. The method is simple, accurate and can be used for quality control and evaluation of A tractylodes macrocephala Koidz.